Analisis Isi Kuantitatif Perlakuan Body Shaming dalam Film Imperfect (Studi Kasus dalam Film Imperfect : Karier, Cinta dan Timbangan) - Utami, Meutia Galuh; Rhafidilla Vebrynda, (Mediakita, 2023)
Movies were created not only to entertain but also to convey the messages depicted in them. There are many movies that raise social issues. An issue becoming a trend is about body shaming. This issue is still considered trivial by Indonesian people even though the impacts is huge for the victims. One of the movies that raises the issue of body shaming is the movie "Imperfect: Karier, Cinta, dan Timbangan (Carrier, Love, and Scale)" (2019) by Ernest Prakasa. This movie depicts the action of body shaming that occurs in everyday life and it indirectly has become a real part of life. This study analyzes the body shaming actions contained in the film. To collect the data, the writer observed the scenes using quantitative content analysis research method. The results show that the frequency of body shaming in the category of commenting on appearance is 7 times, fat shaming is 5 times, commenting on other people's food is 5 times, nicknaming is 4 times, comments on appearance about skin, face shape, and comments through social media is as many as 2 times for each category. Meanwhile, for the category of considering their body fat is as much as 1 time and 10 times for nonverbal body shaming actions from a total of 37 scenes indicated by body shaming actions in the film "Imperfect" with the total reliability test results of 0.91 or 91%. Keywords: Body Shaming; Imperfect Movie; Quantitative Content Analysis